1992
DOI: 10.1002/jbm.820260607
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of fibrinogen adsorption on PEG‐coated polystyrene surfaces

Abstract: Reduction of protein adsorption by coating surfaces with polyethylene glycol (PEG) is well documented. The present work has four goals related to these previous studies: first, to develop chemistry providing densely packed, covalently bound PEG on polystyrene (PS); second, to determine the ability of these modified surfaces to reject fibrinogen; third, to compare the protein-rejecting ability of branched and linear PEGs; and fourth, to examine the utility of an ELISA-type procedure for measuring protein adsorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
105
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 191 publications
(112 citation statements)
references
References 18 publications
6
105
0
1
Order By: Relevance
“…It can be noted that the polymers evaluated in this study all accumulate proteins, in contrast to nonadsorbing "stealth" surfaces based on neutral or zwitterionic polymers such as poly(ethylene oxide) and poly(carboxybetaine methacrylate). [43][44][45][46][47] Considering the in vivo situation, the soft PLMA surface will become covered with proteins, but as indicated in our study, in a rather native conformation. In contrast, a poly(ethylene glycol) modified surface will be free from proteins.…”
Section: D417-5 Fromellmentioning
confidence: 99%
“…It can be noted that the polymers evaluated in this study all accumulate proteins, in contrast to nonadsorbing "stealth" surfaces based on neutral or zwitterionic polymers such as poly(ethylene oxide) and poly(carboxybetaine methacrylate). [43][44][45][46][47] Considering the in vivo situation, the soft PLMA surface will become covered with proteins, but as indicated in our study, in a rather native conformation. In contrast, a poly(ethylene glycol) modified surface will be free from proteins.…”
Section: D417-5 Fromellmentioning
confidence: 99%
“…It has long been established that attachment of PEG to a solid surface inhibits protein adsorption (Bergström et al, 1992;Cheng et al, 1987;Jiang et al, 2003;Szleifer and Carignano, 2000). In this vein, Jeong and co-workers have observed that the extent of protein adsorption to co-polymer blends of PLG and PEG depends upon the PEG molecular weight (Jeong et al, 2000).…”
Section: Introductionmentioning
confidence: 96%
“…PEG is widely recognized for its lack of interactions with macromolecules found in body fluids. [47][48][49] Use of PEG as a spacer arm or tether has been shown to increase the activity of bound enzymes. D'Urso et al 50 found that the K m of enzymes bound to a surface by a PEG tether is increased 10 -20 times over that of the native enzyme.…”
Section: Introductionmentioning
confidence: 99%